Increasing Halal Awareness through Spiritual Capital Awareness Case Study on Traditional Market Traders in Surabaya - Mochammad Soleh (Journal of Halal Product and Research (JHPR), 2022)
Today, news regarding unethical behavior in traditional markets is frequently reported in a variety of mass media. Some of them involve lowering the weights of trading goods, trading or combining high-quality commodities with low-quality ones, and the mystical belief of black magic. Because business players have poor spiritual capital, they are more susceptible to moral hazard, which is harmful to the transaction process and gives rise to this social problem. In order to understand the urgency of social capital in business actors in traditional marketplaces, it is fascinating to analyze this situation. Snowball sampling is used in this study's qualitative phenomenological methodology. The results of research conducted on Muslim traders in traditional markets show that spiritual capital is well understood, even though in practice it is often not realized. An understanding of good spiritual capital has a huge influence on their mindset so it also has an impact on their patterns of economic behavior in conducting trading businesses in accordance with Islamic laws and principles (halal trading).  Keywords: Spiritual Capital, Mindset, Behavior